2012
DOI: 10.1007/s00244-012-9751-x
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of Polybrominated Diphenyl Ethers by the Freshwater Benthic Amphipod Gammarus pulex

Abstract: This study reports on the relationship between polybrominated diphenyl ether (PBDE) levels in water, sediment, and the benthic macroinvertebrate Gammarus pulex, which plays a major ecological role in freshwater ecosystems. Samples were taken in a periurban watershed (near Paris, France), and PBDEs were systematically detected in sediment (≤727 ng g(-1) OC) and G. pulex (≤264 ng g(-1) lipids). PBDEs were also occasionally detected in the water column at low levels (∑ PBDEs < 1.5 ng L(-1)). The log values of bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 51 publications
(57 reference statements)
0
14
0
Order By: Relevance
“…The accumulation of these two congeners in G. pulex is not surprising due to the fact that Tlili et al (2012) have previously demonstrated, in a field study, a PBDEs bioaccumulation in G. pulex. However, our results go further, since we have demonstrated a higher PBDE accumulation in females compared to males.…”
Section: Pbdes Toxicity and Gammarid Gendermentioning
confidence: 81%
See 3 more Smart Citations
“…The accumulation of these two congeners in G. pulex is not surprising due to the fact that Tlili et al (2012) have previously demonstrated, in a field study, a PBDEs bioaccumulation in G. pulex. However, our results go further, since we have demonstrated a higher PBDE accumulation in females compared to males.…”
Section: Pbdes Toxicity and Gammarid Gendermentioning
confidence: 81%
“…To our knowledge, no study was devoted to compare the bioaccumulation of BDE-47 and BDE-99 in freshwater invertebrates in laboratory conditions. However, this result is surprising as several field studies have highlight a greater bioaccumulation of BDE-47 as compared to BDE-99 in various aquatic species as flounder, blue mussel, aquatic oligochaete or amphipods (Christensen et al, 2002;Wu et al, 2008;Ciparis and Hale, 2009;Tlili et al, 2012;Waszak et al, 2012). In our study case, the higher BDE-99 accumulation in G. pulex as compared to BDE-47 accumulation could be explained by the fact that the BDE-99 concentration in the water of exposure was higher than the BDE-47 one, especially at 1 mg L À1 (see Table 1).…”
Section: Dose-and Congener-dependent Impact Of Pbdesmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, the release of PBDEs in ecosystems continues due to their presence in products currently in use and new products manufactured using recycled PBDE-containing material (La Guardia et al 2006). It has been shown that PBDEs, especially BDE-47 and BDE-99 congeners, bioaccumulated in several aquatic organisms such as fish or bivalves (Gustafsson et al 1999;Lema et al 2007;, but also amphipod (Tlili et al 2012;Gismondi and Thomé 2014;Lebrun et al 2014). Despite these observations, only few studies have investigated PBDEs toxic effects on invertebrates.…”
Section: Introductionmentioning
confidence: 99%